2008
DOI: 10.3748/wjg.14.709
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of symptoms of gastroesophageal reflux diseases in type 2 diabetics with neuropathy

Abstract: higher in patients with neuropathy than patients without neuropathy (58.7% vs 32.7%, P < 0.01). The prevalence of heartburn, chest pain and chronic cough are also higher in patients with neuropathy than in patients without neuropathy (43.5% vs 24%; 10.9% vs 4.8% and 17.8% vs 6.7% respectively, P < 0.05). CONCLUSION:The prevalence of GERD symptoms in type 2 DM is higher than in the general population. Our data suggest that DM neuropathy may be an important associated factor for developing GERD symptoms. INTROD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 17 publications
3
97
3
1
Order By: Relevance
“…Embora haja controvérsias, esses sintomas não são considerados causas importantes de mortalidade em pacientes portadores da doença, mas também podem influenciar negativamente a saúde geral e a qualidade de vida 10,15,16 .…”
Section: Sintomas Gastrointestinais No Dmunclassified
“…Embora haja controvérsias, esses sintomas não são considerados causas importantes de mortalidade em pacientes portadores da doença, mas também podem influenciar negativamente a saúde geral e a qualidade de vida 10,15,16 .…”
Section: Sintomas Gastrointestinais No Dmunclassified
“…In many cross-sectional studies using different methodologies, the prevalence of GERD has been reported to be at rates of up to 70% (9)(10)(11)(12)(13)(14)(15). (18), GERD prevalence was found to be 40.7%. Increased BMI in most patients with diabetes may also contribute to the reflux.…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…In the second case, the patient had a past medical history of diabetes mellitus and was diagnosed with acute cerebral infarction, which may alter the motility of the esophageal sphincter and cause retention of the enteral formula. 10 Listed risk factors related to the patients in these two cases might have resulted in the esophageal obstruction observed in these two cases.…”
Section: Discussionmentioning
confidence: 99%